Preparing healthcare providers towards Sustainable Development Goal 3.D.1: International Health Regulations and health emergency preparedness - Ahayalimudin, Nurul'Ain; Seers, Kate; Staniszewska, Sophie (International Islamic University Malaysia, 2019)
Preparing healthcare providers to sustain during the episode of emergency and disaster is critical. Indeed, it is concurrent to the global agenda of Sustainable Development Goal 3.D which has mentioned the target of “Strengthen the capacity of all countries, in particular developing countries, for early warning, risk reduction and management of national and global health risks”. This study aimed to explore the experience of the diverse working background of nurses that have been involved in various disaster since 2004, including emergency physicians. Constructivist grounded theory by Kathy Charmaz was adopted to facilitate this study. About thirty nurses and five emergency physicians were involved in sharing their opinions, views and thoughts about their response during the cataclysmic situation. One-to-one, in-depth and semi-structured interviews were carried out to gain rich data, with an average of forty-five minutes for each session. This study revealed that most of the nurses were unprepared in facing disasters which then leads to the formation of ‘Being A Disaster Nurse’ model. Nurses pointed out three key notions that need to be given attention while preparing them in advance; 1) establishing competencies and responsibilities, 2) getting support and 3) managing emotions. It gives focus on ensuring individual sustainability when in a hostile environment. The discipline of the disaster still in its infancy in Malaysia, as compared to other countries that experience similar situations. Therefore, this study is adding to the current body of knowledge on the healthcare provider’s experiences during disaster responses which could assist the healthcare administrators in giving further attention and preparing them to face and cope with disaster, apart from ensuring their sustainability while responding to any disaster events. This could help to react to the global agenda of strengthening the ‘human’ capacity in preparing the healthcare providers for emergencies and disasters.